Jaminan Konstitusional Hak Politik Warga Negara Indonesia di Luar Negeri Dalam Penyelenggaraan Pemilihan Umum Presiden dan Wakil Presiden 2014 - Dani, Dita Mira (University of Jember, 2015)
The Issues that will be discussed regarding the implementation of constitutional guarantees of the political rights of Indonesian citizens (WNI) abroad in holding the 2014 General Election of the President and Vice President (GEPVP), and analyzing the level of participation of Indonesian citizens (WNI) abroad in holding the General Election of President and Vice President. This paper uses a juridical-normative type, while the research approach used is the constitutional approach and the conceptual approach. The application of constitutional guarantees in the implementation of the 2014 Presidential Election abroad has been guaranteed in the constitution and the Presidential Election Law, however, there are still many Indonesian citizens abroad who have not received their voting rights. This happened due to various weaknesses in the implementation of the 2014 GEPVP abroad, including the problem regarding the multiple Permanent Voters List and the number of Indonesians who were not registered in the DPT. Another problem that was found was the lack of campaign activities abroad which so far only rode on promotional and cultural activities, lack of clarity in socialization activities, regarding ballots via unclear post, and not optimal use of Dropbox. KEYWORDS: Constitutional Guarantee, Political Rights, Indonesian Citizens, General Election of President and Vice President.